2017
DOI: 10.1186/s12992-017-0245-5
|View full text |Cite
|
Sign up to set email alerts
|

Operational and implementation research within Global Fund to Fight AIDS, Tuberculosis and Malaria grants: a situation analysis in six countries

Abstract: BackgroundOperational/implementation research (OR/IR) is a key activity to improve disease control programme performance. We assessed the extent to which malaria and tuberculosis (TB) grants from the Global Fund to Fight AIDS, Tuberculosis and Malaria (“Global Fund”) include support for OR/IR, and discuss the implications of the current Global Fund operating mechanisms for OR/IR support.MethodsThe situation analysis focussed on malaria and TB, while HIV was excluded. Stakeholder interviews were conducted at th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 17 publications
(13 reference statements)
3
22
0
Order By: Relevance
“…A recent publication reviewed the situation of OR among Global Fund grantees across six countries and concluded that countries had varied capacities for implementing OR and required more guidance for the same [59]. This is the first time that an experience of promoting OR through a Global Fund grant is documented.…”
Section: Discussionmentioning
confidence: 99%
“…A recent publication reviewed the situation of OR among Global Fund grantees across six countries and concluded that countries had varied capacities for implementing OR and required more guidance for the same [59]. This is the first time that an experience of promoting OR through a Global Fund grant is documented.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, OR and other evidence-based approaches are not being routinely embedded in control activities funded by the Global Fund despite the effort and advocacy from different stakeholders such as the Special Programme for Research and Training in Tropical Diseases (TDR) and local research organisations. The reasons for this have been previously explored by Kiefer and colleagues [12] revealing considerable variations from one country to another and between programmes with regards to the needs, demands, absorption capacity and funding for OR related to malaria and TB. The study by Kiefer and colleagues remarked the necessity of the involvement of national research coordination bodies, established research agendas and prioritizing human and technical research capacity to strengthen OR locally.…”
Section: Introductionmentioning
confidence: 99%
“…Building on the ndings from Kiefer and colleagues [12], the Swiss Tropical and Public Health Institute (Swiss TPH), commissioned by TDR, undertook a follow-up investigation to nd out if and how an OR tool could become an integral feature in the Global Fund grants. The Structured Operational Research and Training IniTiative (SORT IT), a global partnership coordinated by TDR and implemented with partners, was the main OR reference tool for this investigation of four recipient countries in sub-Saharan Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…and data science(30), with rapid-response calls from major funders(5,(31)(32)(33). However, our data signal a need for a far broader paradigm shift in research design and implementation.…”
mentioning
confidence: 99%